Roles and collaboration of nurses and chaplains in spiritual care: A scoping review - Kamriani Kamriani; Nur Hidayah; Syamsiah Rauf (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Spiritual care is an essential component of holistic healthcare, with equal importance to physical, psychological, and social care. Nurses have the primary responsibility for assessing and addressing patients' spiritual needs, while chaplains or spiritual care providers serve as professional partners who complement spiritual care services, particularly for patients in critical, palliative, and end-of-life settings. However, the implementation of collaborative spiritual care between nurses and chaplains continues to face various challenges. Purpose: This scoping review aimed to map the existing evidence on the roles of nurses and chaplains in providing spiritual care, identify key concepts related to spiritual care competencies, interprofessional collaboration, and barriers to implementation, and explore evidence gaps in the literature, particularly within Indonesia and other Muslim-majority countries. Method: A scoping review was conducted following the Arksey and O'Malley framework, as refined by the Joanna Briggs Institute (JBI). Literature searches were performed in PubMed, CINAHL, Scopus, Google Scholar, and Garuda Portal for studies published between 2021 and 2025. The article selection process followed the PRISMA Extension for Scoping Reviews (PRISMA-ScR) guidelines, resulting in 40 studies that met the inclusion criteria. Results: Three major themes emerged from the synthesis: (1) the roles of nurses, including spiritual assessment, spiritual interventions, patient advocacy, and documentation; (2) the roles of chaplains or spiritual care providers, including spiritual counseling, end-of-life support, mediation among patients, families, and healthcare teams, and education for healthcare professionals; and (3) interprofessional collaboration, demonstrating that integrated spiritual care models contribute to improved patient satisfaction, enhanced quality of care, and reduced spiritual distress. Conclusions: Nurses and chaplains play complementary and indispensable roles in addressing patients' spiritual needs. Strengthening nurses' spiritual care competencies, standardizing chaplain competencies within hospital settings, and developing integrated interprofessional collaboration models are essential strategies for improving the quality of patient-centered spiritual care.